2017
DOI: 10.3389/fpls.2017.00944
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa: Host Range and Advance in Molecular Identification Techniques

Abstract: In the never ending struggle against plant pathogenic bacteria, a major goal is the early identification and classification of infecting microorganisms. Xylella fastidiosa, a Gram-negative bacterium belonging to the family Xanthmonadaceae, is no exception as this pathogen showed a broad range of vectors and host plants, many of which may carry the pathogen for a long time without showing any symptom. Till the last years, most of the diseases caused by X. fastidiosa have been reported from North and South Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 197 publications
(238 reference statements)
0
61
0
3
Order By: Relevance
“…Ulmus species are affected by the subspecies 'multiplex' of X. fastidiosa (Baldi & La Porta, 2017). Pockets of bacterial wetwood rot in U. glabra were recorded by Lindeman (2008).…”
Section: Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…Ulmus species are affected by the subspecies 'multiplex' of X. fastidiosa (Baldi & La Porta, 2017). Pockets of bacterial wetwood rot in U. glabra were recorded by Lindeman (2008).…”
Section: Bacteriamentioning
confidence: 98%
“…Since 2013 several subspecies have become serious economic pests of Olea europaea and citrus trees in Europe (Azevedo, Araujo, & Lacava, ; White, Bullock, Hooftman, & Chapman, ), plus infecting species of Quercus , Platanus and Ulmus , including U. glabra where it causes bacterial leaf scorch (Sherald & Kostka, ). Ulmus species are affected by the subspecies ‘multiplex’ of X. fastidiosa (Baldi & La Porta, ). Pockets of bacterial wetwood rot in U. glabra were recorded by Lindeman ().…”
Section: Herbivory and Diseasementioning
confidence: 99%
“…Several immunological and molecular methods for specific detection of X. fastidiosa have been developed by diverse research groups (comprehensively reviewed by Baldi & La Porta ()). Some of the PCR‐based methods were designed to detect the pathogen at the species level using primers targeted to genomic regions conserved among all subspecies (Francis et al ., ), others to differentiate among a subset of subspecies (Hernandez‐Martinez et al ., ), and yet others to detect a specific subspecies (Pooler & Hartung, ; Brady et al ., ).…”
Section: Coffee Leaf Scorchmentioning
confidence: 99%
“…Nowadays, different molecular tools targeting 54 specific DNA regions are available to detect the bacterium at the species level or to specifically 55 detect one of the subspecies. Conventional PCRs such as Minsavage et al (2014) have been 56 developed, but they are less sensitive than Real-Time PCR (Baldi and La Porta, 2017). Among 57 the real-time PCR techniques developed, the method designed by Harper et al (2010) was 58 identified as one of the most suitable methods for Xf detection.…”
Section: Introductionmentioning
confidence: 99%